1999
DOI: 10.1123/ssj.16.4.348
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Effects of School Sport Experiences on Sport Participation in Later Life

Abstract: This paper presents findings on the relationship between high school sport participation and involvement in sport as adults. The data are provided by a survey of a large representative national sample of adult Canadians. For different age subgroups among women and men, we tested the school sport experiences hypothesis that sport involvement during the high school years contributes to later adult involvement in sport. The measurement of sport involvement in the high school years is concerned with intramural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 20 publications
2
44
0
2
Order By: Relevance
“…In three studies, a non-significant relationship was found in at least one age cohort in female participants [27,43,44]. A significant relationship between adolescent and adult physical activity has also been confirmed by retrospective studies [45][46][47][48]. Among men, the long-term stability of physical activity from adolescence to adulthood seems to be low but significant.…”
Section: Tracking From Childhood and Adolescence To Adulthoodmentioning
confidence: 83%
“…In three studies, a non-significant relationship was found in at least one age cohort in female participants [27,43,44]. A significant relationship between adolescent and adult physical activity has also been confirmed by retrospective studies [45][46][47][48]. Among men, the long-term stability of physical activity from adolescence to adulthood seems to be low but significant.…”
Section: Tracking From Childhood and Adolescence To Adulthoodmentioning
confidence: 83%
“…Analizar este tipo de aspectos durante la adolescencia obedece a la consideración de ésta como una etapa crítica en la que se desarrollan hábitos que pueden ser mantenidos a lo largo de toda la vida y, por lo tanto, objeto de mecanismos y estrategias de promoción de conductas asociadas a estilos de vida saludables. Aunque la evidencia empírica sobre el desarrollo de hábi-tos a lo largo de la vida es escaso, diversas investigaciones apuntan a que éste podría ser el caso en el ámbito del desarrollo de hábitos de actividad físico-deportiva (Curtis, McTeer y White, 1999;Hirvensalo, Lintunen y Rantanen, 2000). Por lo tanto, conocer la práctica físico-deportiva de los adolescentes y sus característi-cas, será fundamental para la toma de decisiones con respecto a la promoción de estilos de vida saludables que incluyan la práctica de este 32 IGOR ESNAOLA Y LORENA REVUELTA / ACCIÓN PSICOLÓGICA, julio 2009, vol.…”
Section: Introductionunclassified
“…Personal experiences of practice of sport in period of school education result in involvement in sport at later periods of life [40] [41]. E. Kozdroń and P. Szczypiorski [42] declare that the hardest thing is to encourage physical activity in the elderly that were inactive earlier in life; but when physical activity becomes their way of life, they rarely give up on it.…”
Section: Running As the Most Popular Form Of Recreation And Sportsmentioning
confidence: 99%